2014
DOI: 10.7861/clinmedicine.14-4-391
|View full text |Cite
|
Sign up to set email alerts
|

A quality assessment of respiratory auscultation material on YouTube

Abstract: YouTube contains a large volume of medical educational material. This study assessed the quality of respiratory auscultation videos contained in YouTube. Videos were searched for using the terms 'breath sounds', 'respiratory sounds', 'respiratory auscultation' and/or 'lung sounds'. In total, 6,022 videos were located, 36 of which were considered suitable for scoring for video accuracy, comprehensiveness and quality. The average score was 3.32/6 (55.3%±1.30). Video score correlated with time-adjusted YouTube me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 19 publications
(33 reference statements)
0
26
0
1
Order By: Relevance
“…They concluded that few of the many video tutorials available on cardiac auscultation on YouTube were accurate. More recently, the same group performed a similar analysis on the quality of YouTube videos focused on respiratory auscultation [28]. Of the 6022 videos located, only 36 met inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that few of the many video tutorials available on cardiac auscultation on YouTube were accurate. More recently, the same group performed a similar analysis on the quality of YouTube videos focused on respiratory auscultation [28]. Of the 6022 videos located, only 36 met inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Although several scoring systems were previously used in the non-orthopaedic literature, none was appropriate for the video content that was being assessed presently, as they were specifically tailored to the context of the clinical examination in question [10,23,28]. As such, included shoulder examination videos were assessed for accuracy with an ordinal customized grading system based on previously established grading criteria [2, 6, 12-14, 17, 20, 21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…also be available for review or possibly for remediation by learners after the demonstration, live performance, or in simulation. Other critical physical exam skills, such as cardiac and respiratory auscultation, have the potential to be taught with YouTube videos, but currently the quality of recordings is highly variable (Camm et al, 2013;Sunderland et al, 2014). Despite some limitations, YouTube has promising potential as a lifelong teaching tool when used for clinical education.…”
Section: Social Media Video Feedmentioning
confidence: 97%
“…Approximately 47.0% to 99.6% of videos were excluded, with the majority of studies excluding > 90.0% of identified videos. Though this varies by medical topic and the specific inclusion/exclusion criteria used, in some studies the search strategies used identified thousands of potentially relevant videos which needed to be screened [14,39,41,43,48,51]. For most of the studies included in the scoping review, a minority of videos, ranging from approximately 14.0% to 62.5%, were found to be educationally useful or of high quality.…”
Section: Papers Identified Inmentioning
confidence: 99%